Integration of innovative technologies for effective library service delivery in Nigeria - Ezeabasili, Augusta Chioma; Idhalama, Ogagaoghene Uzezi (Cybrarians journal, 2025)
This study investigated the integration of innovative technologies for effective library services delivery in Nigeria. Five specific objectives guided the study. Descriptive survey research design was adopted for this study.  The population of the study consists of the practicing librarians who are members of the Nigeria Library association (NLA) Google group official online platform for librarians in Nigeria. The instrument was converted to an online survey using Google form, the online link was posted on the NLA platforms soliciting responses from practicing librarians who are members of the platform. The survey response summary show that 118 practicing librarians participated in the study. The data were retrieved and analyzed using descriptive analysis of tables, frequencies, percentages, mean ratings and standard deviation. The findings revealed that out of the 10 listed innovative technologies for effective library service delivery in Nigeria, more than 50% of practising librarians are aware of four which include: Artificial Intelligence technology, D-space, Social media and Internet of things (IoT), others are not aware of the remaining six, this implies that librarians in Nigeria are aware of just few of the innovative technologies that aids in effective library services delivery. The findings also showed that they have integrated the four innovative technologies they are aware of and they have been very effective in library services delivery. From the findings, a lot were discovered including challenges faced by librarians in integrating innovative technologies in libraries. It was concluded that since the few innovative technologies integrated in Nigerian libraries have been found to improve a lot of services at the library, it can be generalized that they are very effective in library services delivery only if the identified challenges could be dealt with. بحثت هذه الدراسة في تكامل التقنيات المبتكرة لتقديم خدمات مكتبية فعّالة في نيجيريا. استرشدت الدراسة بخمسة أهداف محددة. واعتمدت تصميم بحث المسح الوصفي لهذه الدراسة. يتكون مجتمع الدراسة من أمناء المكتبات الممارسين الأعضاء في منصة جوجل الرسمية لجمعية المكتبات النيجيرية (NLA) على الإنترنت لأمناء المكتبات في نيجيريا. تم تحويل الأداة إلى استبيان عبر الإنترنت باستخدام نموذج جوجل، ونُشر الرابط الإلكتروني على منصات NLA لطلب ردود من أمناء المكتبات الممارسين الأعضاء في المنصة. يُظهر ملخص ردود الاستبيان أن 118 أمين مكتبة ممارسًا شاركوا في الدراسة. تم استرداد البيانات وتحليلها باستخدام التحليل الوصفي للجداول والتكرارات والنسب المئوية ومتوسطات التصنيفات والانحراف المعياري. كشفت النتائج أنه من بين التقنيات العشرة المبتكرة المدرجة لتقديم خدمات المكتبات الفعالة في نيجيريا، فإن أكثر من 50٪ من أمناء المكتبات الممارسين على دراية بأربع منها والتي تشمل: تكنولوجيا الذكاء الاصطناعي، ومساحة D، ووسائل التواصل الاجتماعي، وإنترنت الأشياء (IoT)، والبعض الآخر لا يدركون التقنيات الستة المتبقية، وهذا يعني أن أمناء المكتبات في نيجيريا على دراية بالقليل فقط من التقنيات المبتكرة التي تساعد في تقديم خدمات المكتبات الفعالة. أظهرت النتائج أيضًا أنهم قاموا بدمج التقنيات الأربع المبتكرة التي يعرفونها وكانت فعالة للغاية في تقديم خدمات المكتبات. من النتائج، تم اكتشاف الكثير بما في ذلك التحديات التي يواجهها أمناء المكتبات في دمج التقنيات المبتكرة في المكتبات. وخلص إلى أنه نظرًا لأن التقنيات المبتكرة القليلة المدمجة في المكتبات النيجيرية قد وجدت أنها تعمل على تحسين الكثير من الخدمات في المكتبة، فيمكن تعميمها على أنها فعالة للغاية في تقديم خدمات المكتبات فقط إذا كان من الممكن التعامل مع التحديات المحددة.